Modeling the machined surface quality of an aluminum alloy using the active experiment type - Pop, A B; Ţîţu, M A; Pop, G I; Ţîţu, Ş (IOP conference series. Materials Science and Engineering, 2019)
The surface roughness obtained by the cutting processes has always been a subject of great interest when it is intended to improve the quality of the final product requested by the customer. The objective of this scientific paper involves a comparative study on the tracking of the surface roughness measured both longitudinally and transversely in the direction of the cutting feed movement, following the end-milling process of an aluminum alloy used in the aerospace industry worldwide. Practical experiments have conducted in a prestigious company in the aerospace industry of Romania. Regarding the cutting regime, in terms of milling, a cutting speed was adopted to maintain its constant value at 570 m/min, and the cutting depth and feed per tooth are within the range recommended by the cutting tool manufacturer in aluminum machining. The measuring and control devices used to obtain the experimental data were chosen after careful analysis, such as the surface tester and the electronic microscope. With the help of the obtained data, it was possible to interpret the surface roughness results measured longitudinally in the direction of the feed motion, compared to the roughness measured transversally in the same direction of the cutting tool. Different variations of the surface roughness have highlighted with the help of profiles and microscopic analyses of the machined surfaces. This study is in the category of scientific papers with an extremely high level of applied scientific research using experimental statistical modeling of active type.